Mekanisme Pencairan Dana melalui Surat Perintah Pembayaran (SPP) pada Aplikasi Sakti di BPBPK Provinsi Banten - Vanni Fatimah Zahroh; Intan Maharani; Sri Ayadilah Akhdzulhijah; Purnama Fidyah Handayani; Nurul Rifah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
This study examines the fund disbursement mechanism through the Payment Order (SPP) using the Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) at the Building, Infrastructure, and Area Development Agency (BPBPK) of Banten Province. The background of this research is the increasing demand for transparent, accountable, and efficient public financial management through digital systems in government institutions. The objective of this study is to analyze the procedural stages, identify potential risks, and evaluate the effectiveness of the SAKTI application in supporting the disbursement process. This research employed a descriptive qualitative method through direct observation, documentation review, and interviews conducted during the internship program. The findings indicate that the SPP mechanism is implemented systematically, starting from document verification, data input in the payment module, uploading supporting documents, system validation, to submission to the State Treasury Office. The implementation of SAKTI enhances transparency, traceability, and internal control; however, challenges such as incorrect account coding, incomplete documentation, and occasional system disruptions were identified. Mitigation efforts including checklist implementation and double-checking procedures help reduce these risks. The study implies that digital financial systems significantly contribute to strengthening accountability and efficiency in public sector financial management.